Mercurial > hg > Members > kono > Proof > galois
diff src/nat.agda @ 255:6d1619d9f880
library
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Sat, 09 Jan 2021 10:18:08 +0900 |
parents | nat.agda@2eb62a2a34f2 |
children | 891869ead775 |
line wrap: on
line diff
--- /dev/null Thu Jan 01 00:00:00 1970 +0000 +++ b/src/nat.agda Sat Jan 09 10:18:08 2021 +0900 @@ -0,0 +1,340 @@ +{-# OPTIONS --allow-unsolved-metas #-} +module nat where + +open import Data.Nat +open import Data.Nat.Properties +open import Data.Empty +open import Relation.Nullary +open import Relation.Binary.PropositionalEquality +open import Relation.Binary.Core +open import Relation.Binary.Definitions +open import logic + + +nat-<> : { x y : ℕ } → x < y → y < x → ⊥ +nat-<> (s≤s x<y) (s≤s y<x) = nat-<> x<y y<x + +nat-≤> : { x y : ℕ } → x ≤ y → y < x → ⊥ +nat-≤> (s≤s x<y) (s≤s y<x) = nat-≤> x<y y<x + +nat-<≡ : { x : ℕ } → x < x → ⊥ +nat-<≡ (s≤s lt) = nat-<≡ lt + +nat-≡< : { x y : ℕ } → x ≡ y → x < y → ⊥ +nat-≡< refl lt = nat-<≡ lt + +¬a≤a : {la : ℕ} → suc la ≤ la → ⊥ +¬a≤a (s≤s lt) = ¬a≤a lt + +a<sa : {la : ℕ} → la < suc la +a<sa {zero} = s≤s z≤n +a<sa {suc la} = s≤s a<sa + +refl-≤s : {x : ℕ } → x ≤ suc x +refl-≤s {zero} = z≤n +refl-≤s {suc x} = s≤s (refl-≤s {x}) + +a≤sa : {x : ℕ } → x ≤ suc x +a≤sa {zero} = z≤n +a≤sa {suc x} = s≤s (a≤sa {x}) + +=→¬< : {x : ℕ } → ¬ ( x < x ) +=→¬< {zero} () +=→¬< {suc x} (s≤s lt) = =→¬< lt + +>→¬< : {x y : ℕ } → (x < y ) → ¬ ( y < x ) +>→¬< (s≤s x<y) (s≤s y<x) = >→¬< x<y y<x + +<-∨ : { x y : ℕ } → x < suc y → ( (x ≡ y ) ∨ (x < y) ) +<-∨ {zero} {zero} (s≤s z≤n) = case1 refl +<-∨ {zero} {suc y} (s≤s lt) = case2 (s≤s z≤n) +<-∨ {suc x} {zero} (s≤s ()) +<-∨ {suc x} {suc y} (s≤s lt) with <-∨ {x} {y} lt +<-∨ {suc x} {suc y} (s≤s lt) | case1 eq = case1 (cong (λ k → suc k ) eq) +<-∨ {suc x} {suc y} (s≤s lt) | case2 lt1 = case2 (s≤s lt1) + +n≤n : (n : ℕ) → n Data.Nat.≤ n +n≤n zero = z≤n +n≤n (suc n) = s≤s (n≤n n) + +<→m≤n : {m n : ℕ} → m < n → m Data.Nat.≤ n +<→m≤n {zero} lt = z≤n +<→m≤n {suc m} {zero} () +<→m≤n {suc m} {suc n} (s≤s lt) = s≤s (<→m≤n lt) + +max : (x y : ℕ) → ℕ +max zero zero = zero +max zero (suc x) = (suc x) +max (suc x) zero = (suc x) +max (suc x) (suc y) = suc ( max x y ) + +-- _*_ : ℕ → ℕ → ℕ +-- _*_ zero _ = zero +-- _*_ (suc n) m = m + ( n * m ) + +exp : ℕ → ℕ → ℕ +exp _ zero = 1 +exp n (suc m) = n * ( exp n m ) + +minus : (a b : ℕ ) → ℕ +minus a zero = a +minus zero (suc b) = zero +minus (suc a) (suc b) = minus a b + +_-_ = minus + +m+= : {i j m : ℕ } → m + i ≡ m + j → i ≡ j +m+= {i} {j} {zero} refl = refl +m+= {i} {j} {suc m} eq = m+= {i} {j} {m} ( cong (λ k → pred k ) eq ) + ++m= : {i j m : ℕ } → i + m ≡ j + m → i ≡ j ++m= {i} {j} {m} eq = m+= ( subst₂ (λ j k → j ≡ k ) (+-comm i _ ) (+-comm j _ ) eq ) + +less-1 : { n m : ℕ } → suc n < m → n < m +less-1 {zero} {suc (suc _)} (s≤s (s≤s z≤n)) = s≤s z≤n +less-1 {suc n} {suc m} (s≤s lt) = s≤s (less-1 {n} {m} lt) + +sa=b→a<b : { n m : ℕ } → suc n ≡ m → n < m +sa=b→a<b {0} {suc zero} refl = s≤s z≤n +sa=b→a<b {suc n} {suc (suc n)} refl = s≤s (sa=b→a<b refl) + +minus+n : {x y : ℕ } → suc x > y → minus x y + y ≡ x +minus+n {x} {zero} _ = trans (sym (+-comm zero _ )) refl +minus+n {zero} {suc y} (s≤s ()) +minus+n {suc x} {suc y} (s≤s lt) = begin + minus (suc x) (suc y) + suc y + ≡⟨ +-comm _ (suc y) ⟩ + suc y + minus x y + ≡⟨ cong ( λ k → suc k ) ( + begin + y + minus x y + ≡⟨ +-comm y _ ⟩ + minus x y + y + ≡⟨ minus+n {x} {y} lt ⟩ + x + ∎ + ) ⟩ + suc x + ∎ where open ≡-Reasoning + +sn-m=sn-m : {m n : ℕ } → m ≤ n → suc n - m ≡ suc ( n - m ) +sn-m=sn-m {0} {n} z≤n = refl +sn-m=sn-m {suc m} {suc n} (s≤s m<n) = sn-m=sn-m m<n + +si-sn=i-n : {i n : ℕ } → n < i → suc (i - suc n) ≡ (i - n) +si-sn=i-n {i} {n} n<i = begin + suc (i - suc n) ≡⟨ sym (sn-m=sn-m n<i ) ⟩ + suc i - suc n ≡⟨⟩ + i - n + ∎ where + open ≡-Reasoning + +n-m<n : (n m : ℕ ) → n - m ≤ n +n-m<n zero zero = z≤n +n-m<n (suc n) zero = s≤s (n-m<n n zero) +n-m<n zero (suc m) = z≤n +n-m<n (suc n) (suc m) = ≤-trans (n-m<n n m ) refl-≤s + +n-n-m=m : {m n : ℕ } → m ≤ n → m ≡ (n - (n - m)) +n-n-m=m {0} {zero} z≤n = refl +n-n-m=m {0} {suc n} z≤n = n-n-m=m {0} {n} z≤n +n-n-m=m {suc m} {suc n} (s≤s m≤n) = sym ( begin + suc n - ( n - m ) ≡⟨ sn-m=sn-m (n-m<n n m) ⟩ + suc (n - ( n - m )) ≡⟨ cong (λ k → suc k ) (sym (n-n-m=m m≤n)) ⟩ + suc m + ∎ ) where + open ≡-Reasoning + +0<s : {x : ℕ } → zero < suc x +0<s {_} = s≤s z≤n + +<-minus-0 : {x y z : ℕ } → z + x < z + y → x < y +<-minus-0 {x} {suc _} {zero} lt = lt +<-minus-0 {x} {y} {suc z} (s≤s lt) = <-minus-0 {x} {y} {z} lt + +<-minus : {x y z : ℕ } → x + z < y + z → x < y +<-minus {x} {y} {z} lt = <-minus-0 ( subst₂ ( λ j k → j < k ) (+-comm x _) (+-comm y _ ) lt ) + +x≤x+y : {z y : ℕ } → z ≤ z + y +x≤x+y {zero} {y} = z≤n +x≤x+y {suc z} {y} = s≤s (x≤x+y {z} {y}) + +<-plus : {x y z : ℕ } → x < y → x + z < y + z +<-plus {zero} {suc y} {z} (s≤s z≤n) = s≤s (subst (λ k → z ≤ k ) (+-comm z _ ) x≤x+y ) +<-plus {suc x} {suc y} {z} (s≤s lt) = s≤s (<-plus {x} {y} {z} lt) + +<-plus-0 : {x y z : ℕ } → x < y → z + x < z + y +<-plus-0 {x} {y} {z} lt = subst₂ (λ j k → j < k ) (+-comm _ z) (+-comm _ z) ( <-plus {x} {y} {z} lt ) + +≤-plus : {x y z : ℕ } → x ≤ y → x + z ≤ y + z +≤-plus {0} {y} {zero} z≤n = z≤n +≤-plus {0} {y} {suc z} z≤n = subst (λ k → z < k ) (+-comm _ y ) x≤x+y +≤-plus {suc x} {suc y} {z} (s≤s lt) = s≤s ( ≤-plus {x} {y} {z} lt ) + +≤-plus-0 : {x y z : ℕ } → x ≤ y → z + x ≤ z + y +≤-plus-0 {x} {y} {zero} lt = lt +≤-plus-0 {x} {y} {suc z} lt = s≤s ( ≤-plus-0 {x} {y} {z} lt ) + +x+y<z→x<z : {x y z : ℕ } → x + y < z → x < z +x+y<z→x<z {zero} {y} {suc z} (s≤s lt1) = s≤s z≤n +x+y<z→x<z {suc x} {y} {suc z} (s≤s lt1) = s≤s ( x+y<z→x<z {x} {y} {z} lt1 ) + +*≤ : {x y z : ℕ } → x ≤ y → x * z ≤ y * z +*≤ lt = *-mono-≤ lt ≤-refl + +*< : {x y z : ℕ } → x < y → x * suc z < y * suc z +*< {zero} {suc y} lt = s≤s z≤n +*< {suc x} {suc y} (s≤s lt) = <-plus-0 (*< lt) + +<to<s : {x y : ℕ } → x < y → x < suc y +<to<s {zero} {suc y} (s≤s lt) = s≤s z≤n +<to<s {suc x} {suc y} (s≤s lt) = s≤s (<to<s {x} {y} lt) + +<tos<s : {x y : ℕ } → x < y → suc x < suc y +<tos<s {zero} {suc y} (s≤s z≤n) = s≤s (s≤s z≤n) +<tos<s {suc x} {suc y} (s≤s lt) = s≤s (<tos<s {x} {y} lt) + +≤to< : {x y : ℕ } → x < y → x ≤ y +≤to< {zero} {suc y} (s≤s z≤n) = z≤n +≤to< {suc x} {suc y} (s≤s lt) = s≤s (≤to< {x} {y} lt) + +x<y→≤ : {x y : ℕ } → x < y → x ≤ suc y +x<y→≤ {zero} {.(suc _)} (s≤s z≤n) = z≤n +x<y→≤ {suc x} {suc y} (s≤s lt) = s≤s (x<y→≤ {x} {y} lt) + +open import Data.Product + +minus<=0 : {x y : ℕ } → x ≤ y → minus x y ≡ 0 +minus<=0 {0} {zero} z≤n = refl +minus<=0 {0} {suc y} z≤n = refl +minus<=0 {suc x} {suc y} (s≤s le) = minus<=0 {x} {y} le + +minus>0 : {x y : ℕ } → x < y → 0 < minus y x +minus>0 {zero} {suc _} (s≤s z≤n) = s≤s z≤n +minus>0 {suc x} {suc y} (s≤s lt) = minus>0 {x} {y} lt + +distr-minus-* : {x y z : ℕ } → (minus x y) * z ≡ minus (x * z) (y * z) +distr-minus-* {x} {zero} {z} = refl +distr-minus-* {x} {suc y} {z} with <-cmp x y +distr-minus-* {x} {suc y} {z} | tri< a ¬b ¬c = begin + minus x (suc y) * z + ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} (x<y→≤ a)) ⟩ + 0 * z + ≡⟨ sym (minus<=0 {x * z} {z + y * z} le ) ⟩ + minus (x * z) (z + y * z) + ∎ where + open ≡-Reasoning + le : x * z ≤ z + y * z + le = ≤-trans lemma (subst (λ k → y * z ≤ k ) (+-comm _ z ) (x≤x+y {y * z} {z} ) ) where + lemma : x * z ≤ y * z + lemma = *≤ {x} {y} {z} (≤to< a) +distr-minus-* {x} {suc y} {z} | tri≈ ¬a refl ¬c = begin + minus x (suc y) * z + ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} refl-≤s ) ⟩ + 0 * z + ≡⟨ sym (minus<=0 {x * z} {z + y * z} (lt {x} {z} )) ⟩ + minus (x * z) (z + y * z) + ∎ where + open ≡-Reasoning + lt : {x z : ℕ } → x * z ≤ z + x * z + lt {zero} {zero} = z≤n + lt {suc x} {zero} = lt {x} {zero} + lt {x} {suc z} = ≤-trans lemma refl-≤s where + lemma : x * suc z ≤ z + x * suc z + lemma = subst (λ k → x * suc z ≤ k ) (+-comm _ z) (x≤x+y {x * suc z} {z}) +distr-minus-* {x} {suc y} {z} | tri> ¬a ¬b c = +m= {_} {_} {suc y * z} ( begin + minus x (suc y) * z + suc y * z + ≡⟨ sym (proj₂ *-distrib-+ z (minus x (suc y) ) _) ⟩ + ( minus x (suc y) + suc y ) * z + ≡⟨ cong (λ k → k * z) (minus+n {x} {suc y} (s≤s c)) ⟩ + x * z + ≡⟨ sym (minus+n {x * z} {suc y * z} (s≤s (lt c))) ⟩ + minus (x * z) (suc y * z) + suc y * z + ∎ ) where + open ≡-Reasoning + lt : {x y z : ℕ } → suc y ≤ x → z + y * z ≤ x * z + lt {x} {y} {z} le = *≤ le + +minus- : {x y z : ℕ } → suc x > z + y → minus (minus x y) z ≡ minus x (y + z) +minus- {x} {y} {z} gt = +m= {_} {_} {z} ( begin + minus (minus x y) z + z + ≡⟨ minus+n {_} {z} lemma ⟩ + minus x y + ≡⟨ +m= {_} {_} {y} ( begin + minus x y + y + ≡⟨ minus+n {_} {y} lemma1 ⟩ + x + ≡⟨ sym ( minus+n {_} {z + y} gt ) ⟩ + minus x (z + y) + (z + y) + ≡⟨ sym ( +-assoc (minus x (z + y)) _ _ ) ⟩ + minus x (z + y) + z + y + ∎ ) ⟩ + minus x (z + y) + z + ≡⟨ cong (λ k → minus x k + z ) (+-comm _ y ) ⟩ + minus x (y + z) + z + ∎ ) where + open ≡-Reasoning + lemma1 : suc x > y + lemma1 = x+y<z→x<z (subst (λ k → k < suc x ) (+-comm z _ ) gt ) + lemma : suc (minus x y) > z + lemma = <-minus {_} {_} {y} ( subst ( λ x → z + y < suc x ) (sym (minus+n {x} {y} lemma1 )) gt ) + +minus-* : {M k n : ℕ } → n < k → minus k (suc n) * M ≡ minus (minus k n * M ) M +minus-* {zero} {k} {n} lt = begin + minus k (suc n) * zero + ≡⟨ *-comm (minus k (suc n)) zero ⟩ + zero * minus k (suc n) + ≡⟨⟩ + 0 * minus k n + ≡⟨ *-comm 0 (minus k n) ⟩ + minus (minus k n * 0 ) 0 + ∎ where + open ≡-Reasoning +minus-* {suc m} {k} {n} lt with <-cmp k 1 +minus-* {suc m} {.0} {zero} lt | tri< (s≤s z≤n) ¬b ¬c = refl +minus-* {suc m} {.0} {suc n} lt | tri< (s≤s z≤n) ¬b ¬c = refl +minus-* {suc zero} {.1} {zero} lt | tri≈ ¬a refl ¬c = refl +minus-* {suc (suc m)} {.1} {zero} lt | tri≈ ¬a refl ¬c = minus-* {suc m} {1} {zero} lt +minus-* {suc m} {.1} {suc n} (s≤s ()) | tri≈ ¬a refl ¬c +minus-* {suc m} {k} {n} lt | tri> ¬a ¬b c = begin + minus k (suc n) * M + ≡⟨ distr-minus-* {k} {suc n} {M} ⟩ + minus (k * M ) ((suc n) * M) + ≡⟨⟩ + minus (k * M ) (M + n * M ) + ≡⟨ cong (λ x → minus (k * M) x) (+-comm M _ ) ⟩ + minus (k * M ) ((n * M) + M ) + ≡⟨ sym ( minus- {k * M} {n * M} (lemma lt) ) ⟩ + minus (minus (k * M ) (n * M)) M + ≡⟨ cong (λ x → minus x M ) ( sym ( distr-minus-* {k} {n} )) ⟩ + minus (minus k n * M ) M + ∎ where + M = suc m + lemma : {n k m : ℕ } → n < k → suc (k * suc m) > suc m + n * suc m + lemma {zero} {suc k} {m} (s≤s lt) = s≤s (s≤s (subst (λ x → x ≤ m + k * suc m) (+-comm 0 _ ) x≤x+y )) + lemma {suc n} {suc k} {m} lt = begin + suc (suc m + suc n * suc m) + ≡⟨⟩ + suc ( suc (suc n) * suc m) + ≤⟨ ≤-plus-0 {_} {_} {1} (*≤ lt ) ⟩ + suc (suc k * suc m) + ∎ where open ≤-Reasoning + open ≡-Reasoning + +open import Data.List + +ℕL-inject : {h h1 : ℕ } {x y : List ℕ } → h ∷ x ≡ h1 ∷ y → h ≡ h1 +ℕL-inject refl = refl + +ℕL-inject-t : {h h1 : ℕ } {x y : List ℕ } → h ∷ x ≡ h1 ∷ y → x ≡ y +ℕL-inject-t refl = refl + +ℕL-eq? : (x y : List ℕ ) → Dec (x ≡ y ) +ℕL-eq? [] [] = yes refl +ℕL-eq? [] (x ∷ y) = no (λ ()) +ℕL-eq? (x ∷ x₁) [] = no (λ ()) +ℕL-eq? (h ∷ x) (h1 ∷ y) with h ≟ h1 | ℕL-eq? x y +... | yes y1 | yes y2 = yes ( cong₂ (λ j k → j ∷ k ) y1 y2 ) +... | yes y1 | no n = no (λ e → n (ℕL-inject-t e)) +... | no n | t = no (λ e → n (ℕL-inject e)) +